Comparative analysis of the physique of volleyball players selected from different volleyball clubs - Sieroń, Adrian; Bidzińska, Gabriela (Journal of Education, Health and Sport, 2017)
In recent years we have seen a steady increase in interest in sport among the public. This is due primarily to the deepening of knowledge about the health-promoting aspects for people who practice it regularly. Considerable interest primarily characterized by team games, which due to their accessibility, clearly defined rules, the variety of forms of movement, or finally, the interaction between human are the most popular sport disciplines. In Poland, one of the most popular team sports of football is next to volleyball. From year to year, this form of recreation is more and more supporters. For many years, extremely important for researchers from around the world was to find the factors that determine the achievement of high results volleyball. This problem is steadily gaining in importance, because modern training methods contribute to maximizing the potential of each player. Many researchers believe that making attempts to find factors that are of potential players is one of the few areas where you can find the reserves to increase results. The aim of this study is to compare intergroup somatic athletes practicing volleyball, playing and trainees in four different teams in Lower Silesia. The study enrolled 54 men aged 12-15 years with a group of four volleyball players representing the same level of sports preparation. The study used data measuring 17 somatic features. The results show that the somatic features of individual players in all four teams are similar and homogeneous.